Formability of Aluminum and Steel in Drawing Square Cups - Cloke, Terrance William (My University, 1975)
A series of mechanical formability tests were performed on an aluminum-killed steel and five aluminum alloys. Three of the aluminum alloys exhibited strength levels and strain hardening abilities equal to or better than those of steel, but had very low fracture strains. The other two aluminum alloys had low strength but formed reasonably-well, except for negligible strain hardening ability of one of them. All of the aluminum alloys exhibited planar anisotropy detrimental to deep drawability.
Tooling for deep drawing 2" wide square cups was designed and constructed. Tests were performed to find a suitable lubricant for square cupping tests and a combination of a heavy gear lubricant and polyethylene film was selected.
Tests with the square punch and die set confirmed the results of the mechanical tests. The steel produced the deepest cups while height of cups drawn from the high strength aluminum alloys was severely limited by brittle fracture in the corner walls.
Careful blank development proved to be a definite asset in square cup drawing. The best results were obtained with blanks designed to produce flat-topped cups but some application of blanks with extra material at the corners may be useful for materials exhibiting low fracture strains.
Keywords: Mechanical Engineering; Mechanical Engineering